2023
DOI: 10.1080/19336950.2023.2208928
|View full text |Cite
|
Sign up to set email alerts
|

Identification of SLC2A3 as a prognostic indicator correlated with the NF-κB/EMT axis and immune response in head and neck squamous cell carcinoma

Abstract: SLC2A3 is an important member of the glucose transporter superfamily. It has been recently suggested that upregulation of SLC2A3 is associated with poor survival and acts as a prognostic marker in a variety of tumors. Unfortunately, the prognostic role of SLC2A3 in head and neck squamous cell carcinoma (HNSC) is less known. In the present study, we analyzed SLC2A3 expression in HNSC and its correlation with prognosis using TCGA and GEO databases. The results showed that SLC2A3 mRNA expression was higher in HNS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that GLUT3 is considered a transcriptional target of ZEB1, playing a significant role in lung cancer when tumour cells lose their epithelial features and become more aggressive, promoting lung cancer metastasis [ 14 ]. At the same time, some studies have found that GLUT3 may significantly affect the progression of head and neck squamous cell carcinoma and colorectal cancer cells by regulating EMT [ 18 , 27 ]. Our previous experiment found that GLUT3 was enhanced in the alveolar macrophages of patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that GLUT3 is considered a transcriptional target of ZEB1, playing a significant role in lung cancer when tumour cells lose their epithelial features and become more aggressive, promoting lung cancer metastasis [ 14 ]. At the same time, some studies have found that GLUT3 may significantly affect the progression of head and neck squamous cell carcinoma and colorectal cancer cells by regulating EMT [ 18 , 27 ]. Our previous experiment found that GLUT3 was enhanced in the alveolar macrophages of patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Six genes were not all characterized in cancer. The prognostic predictive potential of SLC2A3 for HNSCC has been reported, and this molecule also mediates cancer cell proliferation and, migration, and immune responses 36 . EFNB2 was identified as a tumor promoter in HNSCC that maximized tumor size and vascular normalization when knocked down in cancer cells and blood vessels 37 .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that Ki-67 is expressed in invasive squamous cell carcinoma tissues, and its expression is closely related to cancer cell proliferation, and also positively correlated with cervical cancer stage [12]. Lee et al [13] reported that p63 promotes the development of normal epithelium and maintains its function, which is of great significance in controlling the consistency of stem cells. It is preferentially expressed in nucleus of cervical reserve cells.…”
Section: Discussionmentioning
confidence: 99%